Low-density high-entropy alloy high-energy beam additive forming method

The method addresses the challenges of preparing refractory high-entropy alloy powders by using high-temperature vacuum suspension melting and plasma spheroidization to produce low-density, high-strength samples with improved sphericity and fluidity, suitable for aerospace applications.

CN119194124APending Publication Date: 2024-12-27AVIC BEIJING INST OF AERONAUTICAL MATERIALS

Patent Information

Application Number
CN202411165842.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing methods for preparing refractory high-entropy alloy powders face challenges such as non-uniform composition, poor sphericity, low fluidity, and high viscosity, leading to issues like cracks and poor plasticity in additive manufacturing processes.

Method used

A method involving high-temperature vacuum suspension melting, hydrogenation-plasma spheroidization, and high-energy beam additive forming to produce low-density high-entropy alloy powders with good sphericity, uniform composition, and high fluidity, followed by laser or electron beam processing to create defect-free samples with high strength and plasticity.

Benefits of technology

The method produces low-density, high-strength, high-plasticity alloy samples with excellent thermal stability and high-temperature performance, suitable for aerospace applications, and achieves high material utilization with low manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194124A_ABST
    Figure CN119194124A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of additive manufacturing, and relates to a low-density high-entropy alloy high-energy beam additive forming method. The method comprises the following steps: smelting an alloy; alloy crushing; ball-milling the powder; spheroidizing the powder; preparing a sample; heat treatment; and sample structure performance detection. The low-density high-entropy alloy sample prepared through high-temperature vacuum suspension smelting and plasma spheroidizing is high in room-temperature compression strength which exceeds 2300 MPa, the ductility exceeds 20%, the compression strength at the temperature of 1000 DEG C exceeds 780 MPa, meanwhile, the low-density high-entropy alloy powder manufacturing problem is solved, and the low-density high-entropy alloy powder manufacturing method is suitable for industrial production. The method has the advantages of good sphericity, good fluidity, uniform components, no hollow powder or satellite powder, low oxygen content and the like, and provides a powerful basis for promoting the application of high-temperature alloy structure new materials in the aerospace field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of additive manufacturing, and in particular relates to a low-density high-entropy alloy high-energy beam additive forming method. Background Art

[0002] Refractory high entropy alloys (RHEAs) are a new type of high entropy alloys with refractory metal elements as the main elements. The refractory metal elements mainly include Hf, Mo, Nb, Ta, and W, and the percentage content of each element is between 5% and 35%. Refractory high entropy alloys have received widespread attention in the aerospace field because of their high melting point, high density and superior high-temperature mechanical properties. Typical RHEAs contain heavy elements (Mo, Ta, W, etc.), which leads to a high density of the alloy, thus limiting the application of RHEAs in various fields. In order to achieve low density and lightweight, researchers have developed the application of lightweight RHEAs in various fields by adding low-density elements (Al, Ti, V, Zr, etc.) in recent years. Compared with traditional RHEAs, lightweight RHEAs not only have high strength, but also have significantly reduced density (density ≤8g / cm 3 ). Lightweight RHEAs have huge differences in elemental properties, which bring strong lattice distortion effect and hysteresis diffusion effect to refractory high-entropy alloys, showing better thermal stability and high-temperature performance.

[0003] Compared with traditional cast high-entropy alloys, powder metallurgy refractory high-entropy alloys can better demonstrate excellent properties such as high hardness, high strength, and excellent corrosion resistance. At the same time, the use of high-energy beam additive manufacturing technology can achieve rapid, low-cost, and high-precision manufacturing, becoming a research hotspot in the field of RHEAs preparation. It provides a limited way to realize additive manufacturing of low-density, lightweight refractory high-entropy alloy components, but there are still problems such as cracks and poor plasticity in the manufacturing process that need to be urgently solved.

[0004] At present, the main methods for preparing high entropy alloy powders are: mechanical alloying, gas atomization and plasma rotating electrode method. Mechanical alloying cannot guarantee the uniformity of composition, sphericity and fluidity of refractory high entropy alloy powders. For example, Chinese patents CN115369274A and CN117758124A use ball milling to prepare CoCrFeNi and AlCrNbTiZrMo high entropy alloys. The gas atomization method and plasma rotating electrode method cannot prepare refractory high entropy alloy powders with high melting points and high viscosities. For example, Chinese patents CN108480615B, CN103056352B, and CN114875291A use gas atomization to prepare FeCoNiCrMoAl and Fe x AlCoCrNiB 0.3 , CuZnMnNiSnSi and other high entropy alloy spherical powders. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a method for high-energy beam additive forming of low-density high-entropy alloys. Through high-temperature vacuum suspension melting and plasma spheroidization, the problem of difficult preparation of refractory high-entropy alloy powders with high melting points and high viscosity is effectively solved, and alloy powders with advantages such as good sphericity, good fluidity, uniform composition, no hollow powder, and low oxygen content are obtained. And through the high-energy beam additive forming method, defect-free, high-strength and high-plasticity alloy samples are prepared, providing process guidance and quality assurance for the additive manufacturing of high-temperature and high-performance high-entropy alloys.

[0006] To solve this technical problem, the technical solution of the present invention is:

[0007] A method for high-energy beam additive forming of a low-density high-entropy alloy, comprising the following steps:

[0008] Step 1: Alloy smelting: Remove the surface oxide scale and clean the high entropy alloy AlMo X Nb (1-X) The TiZr raw materials are converted into a mass ratio according to the atomic percentage of Al:Mo:Nb:Ta:Ti:Zr=1:X:1:(1-X):1:1, and each element raw material is weighed; first, the high-temperature vacuum suspension melting furnace is evacuated and then vacuumized to 1.5×10 -2 Pa, and finally fill with 99.999% high-purity argon to 300-900Pa; put the weighed raw material Ta block into the water-cooled copper crucible in the vacuum suspension melting furnace, increase the heating power from 50kW to 350kW at 30-60kW / min, and after fully melting, maintain the temperature at 3100-3200℃ for 4±2min; reduce the heating power to 270-320kW, add the raw material Mo block to the metal solution through the feeding port, and after fully melting, maintain the temperature at 2600-3100℃ for 4±2min; reduce the heating power to 250-300kW, add the raw material Nb block to the metal solution through the feeding port, and after fully melting, maintain the temperature at 2500-2800℃ ℃, keep warm for 4±2min; reduce the heating power to 200-250kW, add the raw material Zr block into the metal solution through the feeding port, keep the temperature at 1800-2200℃ after it is fully melted, and keep warm for 4±2min; reduce the heating power to 150-200kW, add the raw material Ti block into the metal solution through the feeding port, keep the temperature at 1600-1900℃ after it is fully melted, and keep warm for 4±2min; reduce the heating power to 50-80kW, add the raw material Al block into the metal solution through the feeding port, keep the temperature at 700-800℃ after it is fully melted, and keep warm for 4±2min; increase the heating power to 150-200kW, keep warm for 8±2min, so that the components are fully mixed;

[0009] The heating power is reduced by 20-50kW / min, and the temperature is cooled for 15-30 minutes until the temperature reaches 100°C. The furnace is opened and the alloy ingot is taken out; preferably, water cooling is used. The alloy is repeatedly smelted to obtain a rod-shaped alloy ingot, which is then cooled to below 100°C with the furnace; preferably, the molten metal solution is poured into a rod-shaped water-cooled copper mold using external pressure.

[0010] Step 2, alloy crushing: the rod-shaped alloy ingot is firstly crushed by knocking, and then subjected to hydrogenation treatment. Before hydrogenation, the hydrogenation tank is evacuated and filled with hydrogen, heated to 500°C to 800°C, and kept warm for 2 to 6 hours. After the hydrogenation is completed, 100 to 200 μm refractory high entropy alloy hydride particles are generated;

[0011] Step 3, powder ball milling: mechanically ball milling the refractory high entropy alloy hydride particles, evacuating the ball mill before ball milling and then filling it with argon protection, the rotation speed is 100-300 rpm, the ball milling time is 0-60 min, the forward and reverse ratio is 1:1, and after the ball milling is completed, sieving to obtain irregularly shaped 15-150 μm refractory high entropy alloy hydride powder; preferably, a ball mill or a mechanical crusher is used for ball milling;

[0012] Step 4, powder spheroidization: refractory high entropy alloy hydride powder is prepared into spherical powder, preferably, it is treated by radio frequency induction plasma spheroidization equipment; the refractory high entropy alloy spherical powder is heated to 500-600 ° C in a vacuum furnace, and the temperature is kept for 2-4 hours for dehydrogenation. During the dehydrogenation process, vacuum is continuously drawn to discharge the removed hydrogen. After the dehydrogenation is completed, the temperature is raised to 600-700 ° C, and the temperature is kept for 1-4 hours. After screening, the refractory high entropy alloy powder AlMo is obtained. X Nb (1 -X)TiZr;

[0013] Step 5, sample preparation: Use laser direct deposition molding equipment or electron beam selective melting molding equipment to prepare samples of low-density high-entropy alloy powder. The substrate used is TC4 titanium alloy. During the preparation process, the sample temperature needs to be maintained at 400°C to 800°C, and contact with air should be avoided as much as possible.

[0014] Step 6: Heat treatment: Heat treat the sample in a vacuum heat treatment furnace at 900°C to 1200°C for 3h to 12h, and use argon for rapid cooling to obtain crack-free samples.

[0015] Step 7, tissue performance testing: Process metallographic test specimens and compression performance test specimens, conduct tissue observation and hardness test on the metallographic specimens, and test the compression performance specimens.

[0016] Furthermore, in step 1, the purity of the Ti block, Al block, Mo block, Zr block, Ta block and Nb block is higher than 99.9%.

[0017] Furthermore, the alloy is repeatedly melted in step 1 by placing the alloy ingot back into a water-cooled copper crucible in the vacuum suspension melting furnace, removing air from the high-temperature vacuum suspension melting furnace, and then evacuating the furnace to a temperature of 1.5×10 -2 Pa, fill with 99.999% high-purity argon to 300-900Pa, increase the heating power from 50kW to 200kW at 25kW / min, maintain the temperature at 1600-1900℃, keep warm for 8±1min, then reduce the heating power to 0kW at 20-50kW / min, cool with water for 15-30min, cool to below 100℃, repeat this cycle, and repeatedly melt the alloy for no less than 5 times. The alloy composition is uniform through repeated melting of alloys and precise control of temperature rise and fall, avoiding alloy segregation with large melting point differences and burning of alloy components.

[0018] Furthermore, in the step 4, the refractory high entropy alloy hydride powder is treated by the radio frequency induction plasma spheroidization equipment, which is evacuated and filled with high-purity 99.999% argon for protection, and the relevant parameters are set: the rotation speed is 2 to 15 rpm, the plasma power is 20 to 60 kW, the carrier gas flow rate is 10 to 25 L / min, and the powder feeding rate is 20 to 80 g / min. The powder is heated by a stable plasma torch to form spherical droplets, which enter the heat exchange chamber to solidify and finally fall into the powder collector to obtain spherical alloy powder.

[0019] Furthermore, in step 4, the refractory high entropy alloy powder AlMo X Nb (1-X) The particle size of TiZr is 53-106 μm, the oxygen content is ≤300 ppm, and the bulk density is ≥4 g / cm 3 , fluidity ≤20s / 50g, sphericity ≥0.98.

[0020] Further, in step 5: a laser direct deposition forming device is used to prepare a sample of a low-density high-entropy alloy powder, and the process parameters are laser power 800-5000W, scanning speed 400-800mm / min, powder feeding amount 3-40g / min, powder feeding gas flow 3-15L / min, protective gas flow 10-30L / min, layer thickness 0.3-1.8mm, scanning strategy is serpentine reciprocating, and each layer exchanges the starting point, four layers are a cycle, and induction heating equipment is used during the preparation process to ensure that the sample is at 400-800°C, and the air isolation method is to provide an inert gas protective atmosphere of argon or helium, wherein the oxygen content is within 50ppm. The use of laser direct deposition forming method can achieve low-density high-entropy alloy samples without defects such as inclusions, pores, cracks, etc., and achieve the purpose of high efficiency, high quality, and low cost preparation. At the same time, the size of the prepared sample or component can exceed 1m.

[0021] Further, in step 5: the low-density high-entropy alloy powder is sampled by electron beam selective melting forming equipment, the substrate preheating temperature is 400-800°C, the process parameters are focusing current 20-80mA, current 5-30mA, number of lines 1-5, scanning speed 800-2000mm / s, line spacing 0.2-0.8mm, scanning strategy is serpentine reciprocating, and the vacuum degree is ensured to be 4.5×10 -3 Pa. The electron beam selective melting forming method can realize the integrated preparation of low-density high-entropy alloy complex components, achieving the purpose of high efficiency, high utilization rate and high precision preparation. The thickness of the sample or component can be less than 1mm, and the roughness is higher than Ra3.2mm. The high-entropy alloy obtained by the forming method of the present invention has a low density, which is less than ≤7.5g / cm 3 .

[0022] Furthermore, in step 6: the crack-free sample is confirmed by fluorescence detection according to HB / Z 61.

[0023] Furthermore, in step 7: the size of the metallographic sample is 5mm×5mm×5mm, the size of the compression performance sample is Φ3mm×5mm, the room temperature compression strength is ≥2300MPa, the elongation is 20%, the 1000°C high temperature compression strength is ≥780MPa, and the microhardness is greater than or equal to 620HV.

[0024] Furthermore, in step 7, wire cutting equipment and machine tool equipment are used to process the metallographic specimens and compression performance specimens, so that a specimen with a dense and uniform internal structure can be obtained.

[0025] The beneficial effects of the present invention are:

[0026] 1. The present invention adopts high-temperature vacuum suspension melting alloy ingots, which has good material uniformity, high yield, and few impurities. Ingots with high purity and low impurities can be prepared. At the same time, the method of hydrogenation-plasma spheroidization-dehydrogenation can be used to obtain alloy powders with high sphericity, good fluidity, uniform composition, no hollow powder and satellite powder, and low oxygen content. The alloy powders can be applied to laser direct deposition forming, electron beam selective melting forming, thermal spraying and other process methods. At the same time, the sieved fine powder can be applied to the laser selective melting forming process method;

[0027] 2. The present invention provides a crack-free, low-density, lightweight, refractory high-entropy alloy specimen manufactured by high-energy beam additive manufacturing, which has the obvious advantages of low cost, high material utilization, short manufacturing cycle, high performance, etc., and has a room temperature compressive strength of ≥2300MPa, an elongation of 20%, a high temperature compressive strength of ≥780MPa at 1000°C, and a room temperature microhardness of ≥620HV. The microstructure is a granular B2 phase distributed on a continuous network of BCC, forming a woven network structure, and the grain boundaries contain a small amount of Al-Zr precipitation phase;

[0028] 3. The present invention provides an AlMo X Nb (1-X) The combination ratio of TiZr low-density high-entropy alloy has the characteristics of high strength, high toughness, high wear resistance and high corrosion resistance, and has broad application prospects in important fields such as aerospace. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions implemented in the present invention, the following is a brief explanation of the drawings required to be used in the examples of the present invention. Obviously, the drawings described below are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0030] Figure 1 This is a schematic diagram of the preparation process of low-density high-entropy alloy powder in Example 1;

[0031] Figure 2 This is a scanning electron microscope image of the low-density high-entropy alloy powder in Example 1. Figure 2 (a) (b) are electron microscope images at different magnifications;

[0032] Figure 3 This is a real picture of the laser additive manufacturing sample of the low-density high-entropy alloy in Example 1;

[0033] Figure 4 This is an optical micrograph of the sample of the low-density high-entropy alloy laser additive manufacturing in Example 1; Figure 4 (a) (b) are optical images at different scales;

[0034] Figure 5 This is the EBSD image of the laser additive manufacturing sample of the low-density high-entropy alloy in Example 1;

[0035] Figure 6 This is a real picture of the low-density high-entropy alloy electron beam selected area manufacturing component in Example 2. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0037] The features of various aspects of the embodiments of the present invention will be described in detail below. In the detailed description below, many specific details are proposed to fully understand the present invention. However, it is obvious to those skilled in the art that the present invention can also be implemented without these specific details. The following description of the embodiments is only for a better understanding of the present invention by illustrating examples of the present invention. The present invention is not limited to any specific settings and methods provided below, but covers all product structures, any improvements, replacements, etc. of methods covered without departing from the spirit of the present invention.

[0038] Example 1

[0039] A low-density high-entropy alloy laser direct deposition additive forming method of the present invention comprises the following steps:

[0040] Step 1: Alloy smelting: Remove the surface oxide scale and clean the high entropy alloy AlMo 0.5 Nb 0.5 The TiZr raw materials were converted into mass ratios according to atomic percentages. The raw materials of each element, Al, Mo, Nb, Ta, Ti, and Zr, were weighed to be 6.79%, 13.07%, 23.38%, 22.76%, 12.05%, and 22.95%, respectively. The high-temperature vacuum suspension melting furnace was first evacuated of air, and then vacuumed to 1.5×10 -2Pa, and finally fill with 99.999% high-purity argon to 600Pa; put the weighed 99.95% purity Ta block into the water-cooled copper crucible in the vacuum suspension melting furnace, increase the heating power from 50kW to 350kW at 50kW / min, and after fully melting, maintain the temperature at 3160-3180℃ for 5min; reduce the heating power to 300kW, add the 99.95% purity Mo block into the metal solution through the feeding port, and after fully melting, maintain the temperature at 2950-2970℃ for 5min; reduce the heating power to 280kW, add the 99.95% purity Nb block into the metal solution through the feeding port, and after fully melting, maintain the temperature at 2650-2 670℃, keep warm for 5min; reduce the heating power to 220kW, add the raw material Zr block with purity of 99.95% into the metal solution through the feeding port, after fully melting, keep the temperature at 1960-1980℃, keep warm for 5min; reduce the heating power to 180kW, add the raw material Ti block with purity of 99.95% into the metal solution through the feeding port, after fully melting, keep the temperature at 1840-1860℃, keep warm for 5min; reduce the heating power to 60kW, add the raw material Al block with purity of 99.95% into the metal solution through the feeding port, after fully melting, keep the temperature at 760-780℃, keep warm for 5min; increase the heating power to 180kW, keep warm for 8min, so that the components are fully mixed. The heating power was reduced to 30 kW / min, and the furnace was cooled by water cooling for 20 minutes until the temperature reached 100 °C. The alloy ingot was taken out of the furnace. The alloy was repeatedly smelted and the alloy ingot was put back into the water-cooled copper crucible in the vacuum suspension melting furnace. The high-temperature vacuum suspension melting furnace was evacuated and vacuumized to 1.5×10 -2 Pa, fill with 99.999% high-purity argon gas to 600Pa, increase the heating power from 50kW to 200kW at 25kW / min, maintain the temperature at 1780-1800℃, keep warm for 8min, then reduce the heating power at 30kW / min, cool by water cooling for 20min, cool to 100℃, repeat this cycle, repeatedly smelt the alloy 6 times, finally use external pressure to pour the molten metal solution into a rod-shaped water-cooled copper mold, and cool to below 100℃ with the furnace;

[0041] Step 2, alloy crushing: the rod-shaped alloy ingot is firstly crushed by knocking, and then subjected to hydrogenation treatment. Before hydrogenation, the hydrogenation tank is evacuated and filled with hydrogen, heated to 700°C ± 10°C, and kept warm for 4 hours. After the hydrogenation is completed, 100-200 μm refractory high entropy alloy hydride particles are generated;

[0042] Step 3, powder ball milling: mechanically ball mill the refractory high entropy alloy hydride particles using a ball mill or a mechanical crusher. Before ball milling, the ball mill is first evacuated and then filled with argon gas for protection. The rotation speed is 200 rpm, the ball milling time is 45 minutes, and the forward and reverse ratio is 1:1. After the ball milling is completed, the refractory high entropy alloy powder with an irregular shape of 15 to 150 μm is obtained by sieving;

[0043] Step 4, powder spheroidization: The refractory high entropy alloy hydride powder is treated by radio frequency induction plasma spheroidization equipment, vacuumed and filled with high-purity 99.999% argon protection, and the relevant parameters are set: the rotation speed is 10rpm, the plasma power is 40kW, the carrier gas flow rate is 15L / min, and the powder feeding rate is 45g / min. The powder is heated by a stable plasma torch to form spherical droplets, which enter the heat exchange chamber for solidification and finally fall into the powder collector to obtain spherical alloy powder. Spherical powder is obtained; the refractory high entropy alloy powder is heated to 550℃±10℃ in a vacuum furnace and kept for 4h for dehydrogenation. During the dehydrogenation process, vacuum is continuously drawn to discharge the removed hydrogen. After the dehydrogenation is completed, the temperature is raised to 640℃±10℃ and kept for 3h. After screening, the refractory high entropy alloy powder AlMo is obtained. 0.5 Nb 0.5 TiZr, whose particle size is 53-106 μm, oxygen content is 237 ppm, bulk density is 4.4 g / cm3, fluidity is 13.6 s / 50 g, sphericity is 0.98, and the schematic diagram of the preparation process of low-density high-entropy alloy powder from step 1 to step 4 is shown in the figure. Figure 1 As shown in Figure 2, the alloy powder was observed by SEM. Figure 2 As shown, its composition is measured as follows: Al, Mo, Nb, Ta, Ti, Zr are 7.29%, 12.87%, 22.35%, 22.64%, 11.84%, 22.65% respectively, and the remaining O content is 0.016%, N content is 0.0132%, and H content is 0.00408%;

[0044] Step 5, sample preparation: laser direct deposition forming equipment is used to prepare the sample of low-density high-entropy alloy powder. The process parameters are laser power 1500W, scanning speed 800mm / min, powder feeding amount 5g / min, powder feeding gas flow 5L / min, shielding gas flow 20L / min, layer thickness 0.6mm, scanning strategy is serpentine reciprocating, and the starting point is exchanged for each layer, four layers are a cycle, the substrate used is TC4 titanium alloy, the size is 35mm×15mm×30mm, induction heating equipment is used during the preparation process to keep the sample temperature at 600℃±10℃, and in an atmosphere with an oxygen content of 46ppm. The appearance of the low-density high-entropy alloy sample after preparation is as follows Figure 3 (a) shown.

[0045] Step 6: Heat treatment: The sample is heat treated in a vacuum heat treatment furnace with a vacuum degree of 0.8×10 -3 Pa, heating rate 8℃ / min, 1100℃, keep warm for 3h, cool to 80℃ with the furnace, all can obtain the sample with no crack confirmed by fluorescence detection according to HB / Z 61, the results are as follows Figure 3 (b) as shown.

[0046] Step 7, organizational performance testing: Use wire cutting equipment and machine tool equipment to process metallographic specimens and compression performance specimens. The size of the metallographic specimen is 5mm×5mm×5mm, and the size of the compression specimen is Φ3mm×5mm. The organization of the metallographic specimen is observed, and the results are as follows: Figure 4 As shown in the figure, it can be seen that the internal structure is dense and uniform without defects, and is mainly equiaxed crystals. The sample was analyzed by TEM, and the results are as follows Figure 5 As shown in the figure, it can be clearly observed that the A region inside the alloy grain is determined to be the BCC phase, while the B region corresponds to the B2 phase, and there is a small amount of Al-Zr precipitation phase (HCP structure). The microhardness test of the metallographic sample and the compression performance test of the sample are shown in Table 1.

[0047] Table 1

[0048]

[0049] Example 2

[0050] A low-density high-entropy alloy electron beam selective melting additive forming method of the present invention comprises the following steps:

[0051] Step 1: Alloy smelting: Remove the surface oxide scale and clean the high entropy alloy AlMo 0.5 Nb 0.5 The TiZr raw materials were converted into mass ratios according to atomic percentages. The raw materials of each element, Al, Mo, Nb, Ta, Ti, and Zr, were weighed to be 6.79%, 13.07%, 23.38%, 22.76%, 12.05%, and 22.95%, respectively. The high-temperature vacuum suspension melting furnace was first evacuated of air, and then vacuumed to 1.5×10 -2Pa, and finally fill with 99.999% high-purity argon to 500Pa; put the weighed 99.95% purity Ta block into the water-cooled copper crucible in the vacuum suspension melting furnace, increase the heating power from 50kW to 350kW at 50kW / min, and after fully melting, maintain the temperature at 3100-3200℃ for 4min; reduce the heating power to 310kW, add the 99.95% purity Mo block into the metal solution through the feeding port, and after fully melting, maintain the temperature at 2600-3100℃ for 4min; reduce the heating power to 270kW, add the 99.95% purity Nb block into the metal solution through the feeding port, and after fully melting, maintain the temperature at 2500-2 800℃, keep warm for 4min; reduce the heating power to 230kW, add the raw material Zr block with a purity of 99.95% into the metal solution through the feeding port, after fully melting, keep the temperature at 1800-2200℃, and keep warm for 4min; reduce the heating power to 170kW, add the raw material Ti block with a purity of 99.95% into the metal solution through the feeding port, after fully melting, keep the temperature at 1600-1900℃, and keep warm for 4min; reduce the heating power to 65kW, add the raw material Al block with a purity of 99.95% into the metal solution through the feeding port, after fully melting, keep the temperature at 700-800℃, and keep warm for 4min; increase the heating power to 170kW, keep warm for 8min, so that the components are fully mixed. The heating power was reduced by 20-50 kW / min, and the furnace was cooled by water cooling for 15-30 minutes until the temperature reached 100°C. The alloy ingot was taken out of the furnace. The alloy was repeatedly smelted and the alloy ingot was put back into the water-cooled copper crucible in the vacuum suspension melting furnace. The high-temperature vacuum suspension melting furnace was evacuated and vacuumized to 1.5×10 -2 Pa, fill with 99.999% high-purity argon gas to 600Pa, increase the heating power from 50kW to 200kW at 25kW / min, maintain the temperature at 1600-1900℃, keep warm for 8±1min, then reduce the heating power by 20-50kW, cool by water cooling for 15-30min, cool to 100℃, repeat this cycle, repeatedly smelt the alloy 6 times, finally use external pressure to pour the molten metal solution into a rod-shaped water-cooled copper mold, and cool to below 100℃ with the furnace;

[0052] Step 2, alloy crushing: the rod-shaped alloy ingot is firstly crushed by knocking, and then subjected to hydrogenation treatment. Before hydrogenation, the hydrogenation tank is evacuated and filled with hydrogen, heated to 700°C ± 10°C, and kept warm for 4 hours. After the hydrogenation is completed, 100-200 μm refractory high entropy alloy hydride particles are generated;

[0053] Step 3, powder ball milling: mechanically ball mill the refractory high entropy alloy hydride particles using a ball mill or a mechanical crusher. Before ball milling, the ball mill is first evacuated and then filled with argon gas for protection. The rotation speed is 200 rpm, the ball milling time is 45 minutes, and the forward and reverse ratio is 1:1. After the ball milling is completed, the refractory high entropy alloy powder with an irregular shape of 15 to 150 μm is obtained by sieving;

[0054] Step 4, powder spheroidization: The refractory high entropy alloy hydride powder is treated by radio frequency induction plasma spheroidization equipment, vacuumed and filled with high-purity 99.999% argon protection, and the relevant parameters are set: the rotation speed is 10rpm, the plasma power is 40kW, the carrier gas flow rate is 15L / min, and the powder feeding rate is 45g / min. The powder is heated by a stable plasma torch to form spherical droplets, which enter the heat exchange chamber for solidification and finally fall into the powder collector to obtain spherical alloy powder. Spherical powder is obtained; the refractory high entropy alloy powder is heated to 550℃±10℃ in a vacuum furnace and kept for 4h for dehydrogenation. During the dehydrogenation process, vacuum is continuously drawn to discharge the removed hydrogen. After the dehydrogenation is completed, the temperature is raised to 640℃±10℃ and kept for 3h. After screening, the refractory high entropy alloy powder AlMo is obtained. 0.5 Nb 0.5 TiZr, with a particle size of 53-106 μm, an oxygen content of 256 ppm, and a bulk density of 4.3 g / cm 3 , the fluidity is 14.6s / 50g, the sphericity is 0.99, and the chemical composition of the powder is tested by ICP. The results are: Al, Mo, Nb, Ta, Ti, Zr are 7.39%, 12.67%, 22.25%, 22.54%, 11.64%, 22.35% respectively. The remaining O content is 0.019%, N content is 0.0165%, and H content is 0.00608% as measured by oxygen, nitrogen and hydrogen tester;

[0055] Step 5, sample or component preparation: The low-density high-entropy alloy powder was prepared by electron beam selective melting forming equipment. The substrate preheating temperature was 600℃±10℃. The process parameters were focusing current 25mA, current 15mA, line number 1, scanning speed 1200mm / s, line spacing 0.25mm, and scanning strategy was serpentine reciprocating. The vacuum degree was ensured to be 4.2×10 -3 Pa, the sample printing size is φ15mm*10mm, the component printing size is: φ235mm*24mm, the actual object is as follows Figure 6 As shown;

[0056] Step 6: Heat treatment: The sample is heat treated in a vacuum heat treatment furnace with a vacuum degree of 0.75×10 -3Pa, heating rate 9℃ / min, 1100℃, holding for 4h, cooling to 80℃ with the furnace, all can obtain samples with no cracks confirmed by fluorescence detection according to HB / Z 61;

[0057] Step 7, tissue performance test: Use wire cutting equipment and machine tool equipment to process metallographic samples and compression performance samples. The size of the metallographic sample is 5mm×5mm×5mm, and the size of the compression performance sample is Φ3mm×5mm. The compressive strength of the compression performance sample at room temperature is 2350MPa, the elongation is 22.1%, and the microhardness is 658HV. The compressive strength of the high temperature compression performance at 1000 degrees Celsius is 791MPa. Through the metallographic microscope, it can be seen that the internal structure is dense and uniform without defects, mainly equiaxed crystals.

[0058] In order to illustrate the influence of the powder making process and the heat treatment process of the component on the microstructure and performance of the high entropy alloy, Example 3 and Comparative Example 1 were prepared as follows.

[0059] Example 3

[0060] Step 1, alloy smelting: the surface oxide scale of the high entropy alloy AlMo0.3NbTa0.7TiZr raw material is removed and cleaned, and the mass ratio is converted according to the atomic percentage, and the raw materials of each element Al, Mo, Nb, Ta, Ti, and Zr are weighed to be 6.51%, 6.95%, 22.42%, 30.56%, 11.55%, and 22.01% respectively, and the raw materials are placed in a high-temperature vacuum suspension melting furnace in order according to the melting point to be fully melted, and the temperature is 6 temperatures ranging from 700 to 3200°C, and the holding time at each temperature is 5 minutes, and the alloy is repeatedly smelted 6 times;

[0061] Step 2, alloy crushing: knocking and crushing, hydrogenation treatment, evacuating the hydrogenation tank and filling it with hydrogen, heating to 750℃±10℃, keeping warm for 3h, after hydrogenation is completed, 150-200μm refractory high entropy alloy hydride particles are generated;

[0062] Step 3, powder ball milling: before ball milling, the ball milling tank is first evacuated and then filled with argon gas for protection, the rotation speed is 250 rpm, the ball milling time is 60 min, the forward and reverse ratio is 1:1, and after the ball milling is completed, the irregularly shaped refractory high entropy alloy powder of 53-150 μm is obtained by sieving;

[0063] Step 4, powder spheroidization: The irregular alloy powder is subjected to radio frequency induction plasma spheroidization, and the process parameters are a rotation speed of 10rpm, a plasma power of 45kW, a carrier gas flow rate of 20L / min, and a powder feeding rate of 50g / min. The refractory high entropy alloy powder is heated to 550℃±10℃ in a vacuum furnace and kept for 4h for dehydrogenation. During the dehydrogenation process, vacuum is continuously drawn to discharge the removed hydrogen. After the dehydrogenation is completed, the temperature is raised to 650℃±10℃ and kept for 3h. The particle size is 53-106μm, and the oxygen content is The content is 317ppm, the bulk density is 4.5g / cm3, the fluidity is 15.6s / 50g, the sphericity is 0.98, and the chemical composition of the powder is tested by ICP. The results are: Al, Mo, Nb, Ta, Ti, Zr are 6.37%, 6.68%, 22.56%, 30.04%, 10.64%, 19.75% respectively. The remaining O content is 0.016%, N content is 0.0138%, and H content is 0.00808% as measured by the oxygen, nitrogen and hydrogen tester;

[0064] Step 5, sample or component preparation: The sample was prepared by laser direct deposition forming method, and the process parameters were as follows: laser power 2000W, scanning speed 750mm / min, powder feeding amount 8g / min, powder feeding gas flow rate 10L / min, shielding gas flow rate 25L / min, layer thickness 0.8mm, scanning strategy was serpentine reciprocating, and the starting point was exchanged for each layer, four layers were a cycle, and the substrate used was TC4 titanium alloy with a size of 35mm×15mm×30mm;

[0065] Step 6: Heat treatment: vacuum degree 0.85×10 -3 Pa, heating rate 8℃ / min, 1080℃, keep warm for 4h, cool to 80℃ with the furnace;

[0066] Step 7, tissue performance test: Use wire cutting equipment and machine tool equipment to process the metallographic specimens and compression performance specimens. The compressive strength of the compression performance specimen at room temperature is 2389MPa, the elongation is 22.1%, and the microhardness is 687HV. The compressive strength of the high temperature compression performance at 1000℃ is 821MPa. Through the metallographic microscope, it can be seen that the internal structure is dense and uniform without defects, and is mainly equiaxed crystals.

[0067] The density comparison between the low-density high-entropy alloys in Examples 1-3 and the existing high-temperature alloys is shown in Table 2 below. It can be seen that the high-entropy alloys obtained by the forming method of the present invention have a lower density, which is less than ≤7.5 g / cm 3 .

[0068] Table 2

[0069] alloy <![CDATA[Density / g / cm 3 > GH4169 high temperature alloy 8.19 GH5188 high temperature alloy 9.09 Example 1 Low-density high-entropy alloy 7.38 Example 2 Low-density high-entropy alloy 7.39 Example 3 Low-density high-entropy alloy 7.37

[0070] Comparative Example 1

[0071] Step 1, alloy smelting: the surface oxide scale of the high entropy alloy AlMo0.3NbTa0.7TiZr raw material is removed and cleaned, and the mass ratio is converted according to the atomic percentage, and the raw materials of each element Al, Mo, Nb, Ta, Ti, and Zr are weighed to be 6.51%, 6.95%, 22.42%, 30.56%, 11.55%, and 22.01% respectively, and the raw materials are placed in a high-temperature vacuum suspension melting furnace in order according to the melting point to be fully melted, and the temperature is 700-3200°C, and the holding time at each temperature is 3min, and the alloy is repeatedly smelted 4 times;

[0072] Step 2, alloy crushing: knocking and crushing, hydrogenation treatment, evacuating the hydrogenation tank and filling it with hydrogen, heating to 350℃±10℃, keeping warm for 2h, after hydrogenation is completed, 150~200μm refractory high entropy alloy hydride particles are generated;

[0073] Step 3, powder ball milling: before ball milling, the ball milling tank is first evacuated and then filled with argon gas for protection, the rotation speed is 150 rpm, the ball milling time is 30 min, the forward and reverse ratio is 1:1, and after the ball milling is completed, the irregularly shaped refractory high entropy alloy powder of 53-150 μm is obtained by sieving;

[0074] Step 4, powder spheroidization: The irregular alloy powder is subjected to radio frequency induction plasma spheroidization, and the process parameters are a rotation speed of 10rpm, a plasma power of 25kW, a carrier gas flow rate of 20L / min, and a powder feeding rate of 30g / min. The refractory high entropy alloy powder is heated to 550℃±10℃ in a vacuum furnace and kept for 4h for dehydrogenation. During the dehydrogenation process, vacuum is continuously drawn to discharge the removed hydrogen. After the dehydrogenation is completed, the temperature is raised to 450℃±10℃ and kept for 1h. The particle size is 53-106μm, and the oxygen The content is 637ppm, the bulk density is 3.5g / cm3, the fluidity is 26.7s / 50g, the sphericity is 0.89, and the chemical composition of the powder is tested by ICP. The results are: Al, Mo, Nb, Ta, Ti, Zr are 5.37%, 5.98%, 24.78%, 32.27%, 9.64%, 21.35% respectively. The remaining O content is 0.056%, N content is 0.0837%, and H content is 0.0945% as measured by the oxygen, nitrogen and hydrogen tester.

[0075] Step 5, sample or component preparation: The sample is prepared by laser direct deposition forming method, and its process parameters are laser power 4000W, scanning speed 600mm / min, powder feeding amount 15g / min, powder feeding gas flow 10L / min, shielding gas flow 15L / min, layer thickness 1.5mm, scanning strategy is serpentine reciprocating, and each layer exchanges the starting point, four layers are a cycle, the substrate used is TC4 titanium alloy, the size is 35mm×15mm×30mm, and induction heating equipment is used during the preparation process to keep the sample temperature at 200℃±10℃, and in an atmosphere with an oxygen content of 146ppm;

[0076] Step 6: Heat treatment: vacuum degree 1×10 -2 Pa, heating rate 8℃ / min, 800℃, keep warm for 2h, cool to 80℃ with the furnace;

[0077] Step 7, tissue performance test: Use wire cutting equipment and machine tool equipment to process the metallographic specimens and compression performance specimens. The compressive strength of the compression performance specimen at room temperature is 1998MPa, the elongation is 18.3%, and the microhardness is 610HV. The compressive strength of the high temperature compression performance at 1000℃ is 550MPa. Through the metallographic microscope, it can be seen that the internal structure is coarse, mainly equiaxed crystals.

[0078] By comparing Example 3 with the comparative example, it can be seen that with repeated smelting of elemental raw materials at multiple different temperatures and matching the appropriate holding time, the segregation of the alloy is avoided, and the alloy crushing adopts the appropriate hydrogenation process, spheroidization and dehydrogenation process. In contrast, using the powder making process in Comparative Example 1, the sphericity, composition, fluidity, etc. of the alloy powder are lower than those of Example 3, and after the sample preparation and organizational performance testing steps, they are also lower than those of Examples 1 to 3. This is mainly related to the characteristics of the prepared alloy powder, the sample preparation parameters and the heat treatment process, which affects the high entropy alloy AlMo. 0.3 Nb 0.7 Microstructure and properties of TiZr.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should all be covered within the protection scope of the present invention.

Claims

1. A method for high-energy beam additive forming of low-density high-entropy alloys, characterized in that: The steps include: Step 1: Alloy smelting: Remove the surface oxide scale and clean the high entropy alloy AlMo X Nb (1-X) The TiZr raw materials are converted into a mass ratio according to the atomic percentage of Al:Mo:Nb:Ta:Ti:Zr=1:X:1:(1-X):1:1, and each element raw material is weighed; first, the high-temperature vacuum suspension melting furnace is evacuated and then vacuumized to 1.5×10 -2 Pa, and finally fill with 99.999% high-purity argon gas to 300-900Pa; Put the weighed raw material Ta block into the water-cooled copper crucible in the vacuum suspension melting furnace, increase the heating power from 50kW to 350kW at 30-60kW / min, and after fully melting, maintain the temperature at 3100-3200℃ for 4±2min; reduce the heating power to 270-320kW, add the raw material Mo block to the metal solution through the feeding port, and after fully melting, maintain the temperature at 2600-3100℃ for 4±2min; reduce the heating power to 250-300kW, add the raw material Nb block to the metal solution through the feeding port, and after fully melting, maintain the temperature at 2500-2 800℃, keep warm for 4±2min; reduce the heating power to 200-250kW, add the raw material Zr block into the metal solution through the feeding port, keep the temperature at 1800-2200℃ after it is fully melted, and keep warm for 4±2min; reduce the heating power to 150-200kW, add the raw material Ti block into the metal solution through the feeding port, keep the temperature at 1600-1900℃ after it is fully melted, and keep warm for 4±2min; reduce the heating power to 50-80kW, add the raw material Al block into the metal solution through the feeding port, keep the temperature at 700-800℃ after it is fully melted, and keep warm for 4±2min; Increase the heating power to 150-200kW, keep warm for 8±2min to fully mix the ingredients; reduce the heating power to 20-50kW / min, cool for 15-30min, cool to 100℃, open the furnace and take out the alloy ingot; repeatedly smelt the alloy to finally obtain a rod-shaped alloy ingot, and cool it to below 100℃ with the furnace; Step 2, alloy crushing: the rod-shaped alloy ingot is firstly crushed by knocking, and then subjected to hydrogenation treatment. Before hydrogenation, the hydrogenation tank is evacuated and filled with hydrogen, heated to 500°C to 800°C, and kept warm for 2 to 6 hours. After the hydrogenation is completed, 100 to 200 μm refractory high entropy alloy hydride particles are generated; Step 3, powder ball milling: mechanically ball milling the refractory high entropy alloy hydride particles, evacuating the ball mill before ball milling and then filling it with argon protection, the rotation speed is 100-300 rpm, the ball milling time is 0-60 min, the forward and reverse ratio is 1:1, and after the ball milling is completed, sieving to obtain irregularly shaped 15-150 μm refractory high entropy alloy hydride powder; Step 4, powder spheroidization: spherical powder is prepared by using refractory high entropy alloy hydride powder; the refractory high entropy alloy spherical powder is heated to 500-600°C in a vacuum furnace, and kept warm for 2-4 hours for dehydrogenation. During the dehydrogenation process, vacuum is continuously drawn to discharge the removed hydrogen. After the dehydrogenation is completed, the temperature is raised to 600-700°C, and kept warm for 1-4 hours. After screening, the refractory high entropy alloy powder AlMo is obtained. X Nb (1-X) TiZr; Step 5, sample preparation: Use laser direct deposition molding equipment or electron beam selective melting molding equipment to prepare samples of low-density high-entropy alloy powder according to the procedures of digital model or specified size samples. The substrate used is TC4 titanium alloy. During the preparation process, the sample temperature must be maintained at 400°C to 800°C and avoid contact with air; Step 6: Heat treatment: heat treat the sample with a vacuum degree of 1×10 -3 Pa, heating rate 7-10℃ / min, 900℃~1200℃, keep warm for 3h~12h, and obtain crack-free specimens with furnace cooling; Step 7, tissue performance testing: Process metallographic test specimens and compression performance test specimens, conduct tissue observation and hardness test on the metallographic specimens, and test the compression performance specimens.

2. The method according to claim 1, characterized in that In step 1, the purity of the Ti block, Al block, Mo block, Zr block, Ta block and Nb block is higher than 99.9%.

3. The method according to claim 1, characterized in that In step 1, the alloy is repeatedly melted by placing the alloy ingot back into the water-cooled copper crucible in the vacuum suspension melting furnace, removing air from the high-temperature vacuum suspension melting furnace, and then evacuating the furnace to a vacuum of 1.5×10 -2 Pa, fill with 99.999% high-purity argon to 300-900Pa, increase the heating power from 50kW to 200kW at 25kW / min, maintain the temperature at 1600-1900℃, keep warm for 8±1min, then reduce the heating power at 20-50kW / min, cool with water for 15-30min, cool to 100℃, and repeat this cycle, and smelt the alloy repeatedly for not less than 5 times.

4. The method according to claim 1, characterized in that In the step 4, the refractory high entropy alloy hydride powder is treated by radio frequency induction plasma spheroidization equipment, which is evacuated and filled with high-purity 99.999% argon for protection, and the relevant parameters are set: the rotation speed is 2 to 15 rpm, the plasma power is 20 to 60 kW, the carrier gas flow rate is 10 to 25 L / min, and the powder feeding rate is 20 to 80 g / min. The powder is heated by a stable plasma torch to form spherical droplets, which enter the heat exchange chamber to solidify and finally fall into the powder collector to obtain spherical alloy powder.

5. The method according to claim 1, characterized in that In step 4, the refractory high entropy alloy powder AlMo X Nb (1-X) The particle size of TiZr is 53-106 μm, the oxygen content is ≤300 ppm, and the bulk density is ≥4 g / cm 3 , fluidity ≤20s / 50g, sphericity ≥0.

98.

6. The method according to claim 1, characterized in that In the step 5: a laser direct deposition molding device is used to prepare a sample of a low-density high-entropy alloy powder, and the process parameters are: laser power 800-5000W, scanning speed 400-800mm / min, powder feeding amount 3-40g / min, powder feeding gas flow rate 3-15L / min, protective gas flow rate 10-30L / min, layer thickness 0.3-1.8mm, scanning strategy is serpentine reciprocating, and the starting point is exchanged for each layer, four layers are a cycle, and induction heating equipment is used during the preparation process to ensure that the sample is at 400-800°C, and the air isolation method is to provide an inert gas protective atmosphere of argon or helium, wherein the oxygen content is within 50ppm.

7. The method according to claim 1, characterized in that In the step 5, the low-density high-entropy alloy powder is sampled by electron beam selective melting forming equipment, the process parameters are focusing current 20-80 mA, current 5-30 mA, number of lines 1-5, scanning speed 800-2000 mm / s, line spacing 0.2-0.8 mm, scanning strategy is serpentine reciprocating, substrate preheating temperature is 400-800 ° C during the preparation process, and the air isolation method is to provide a vacuum environment, wherein the vacuum degree is 4.5×10 - 3 Within Pa.

8. The method according to claim 1, characterized in that In step 6: the crack-free sample is confirmed by fluorescence detection according to HB / Z61.

9. The method according to claim 1, characterized in that: In step 7: the size of the metallographic sample is 5mm×5mm×5mm, the size of the compression performance sample is Φ3mm×5mm, the room temperature compression strength is ≥2200MPa, the elongation is ≥20%, the 1000°C high temperature compression strength is ≥600MPa, and the microhardness is greater than or equal to 620HV.

10. The method according to claim 1, characterized in that In step 7, wire cutting equipment and machine tool equipment are used to process metallographic specimens and compression performance specimens.

Citation Information

Patent Citations

  • High-entropy alloy powder materials for supersonic spraying and their preparation methods

    CN103056352B

  • A high-entropy alloy powder, its preparation method, and its application in 3D printing.

    CN108480615B

  • High-entropy alloy powder and preparation method thereof and high-entropy alloy laser cladding layer and preparation method thereof

    CN114875291A

  • Preparation method of CoCrFeNi high-entropy alloy powder with superfine single-phase structure

    CN115369274A

  • Refractory high-entropy alloy powder and preparation method thereof

    CN117758124A

Cited By

  • Preparation method and 3D printing method of niobium-tungsten alloy spherical powder

    CN120901289A

  • Preparation method of niobium-tungsten alloy spherical powder and 3D printing method thereof

    CN120901289B

  • Laser additive manufacturing method for high-density low-defect molybdenum-rhenium alloy part

    CN120984900A